Strength of preference and decisions under risk - Carlos Alós-Ferrer; Michele Garagnani (University of Zurich, Department of Economics, 2022)
Influential economic approaches as random utility models assume a monotonic relation between choice frequencies and "strength of preference," in line with widespread evidence from the cognitive sciences, which also document an inverse relation to response times. However, for economic decisions under risk, these effects are largely untested, because models used to fit data assume them. Further, the dimension underlying strength of preference remains unclear in economics, with candidates including payoff-irrelevant numerical magnitudes. We provide a systematic, out-of-sample empirical validation of these relations (both for choices and response times) relying on both a new experimental design and simulations.
Keywords: D01; D81; D91; 330; Stochastic choice; strength of preference; decision errors; risk attitude; Entscheidungsfindung; Skalierung; Risikoverhalten; Nutzenfunktion